The Impact of Work Environment and Work Family Conflict on Job Satisfaction With Work Life Balance as Intervening Variable - Zahra, Fathimatuz; Fazlurrahman, Hujjatullah (CV ODIS, 2023)
The purpose of this study was to test and analyze the effect of work environment and work family conflict on job satisfaction with work life balance as a mediating variable. This research is causality research with a quantitative approach. The sampling technique used saturated samples with a total of 54 respondents at PT Dakwah Inti Media. The statistical analysis used in this research is partial least square with the help of SmartPLS 3.2.9 software. The result of the analysis obtained from this study indicate that work environment has a positive and significant effect on job satisfaction; work family conflict has negative and significant effect on job satisfaction; work life balance has a positive and non-significant effect on job satisfaction; work environment has a positive and non-significant effect on work life balance; work family conflict has a positive and significant effect on work life balance; work life balance in this study has not been able to mediate the effect of work environment on job satisfaction; work life balance in this study has not been able to mediate the effect of work family conflict on job satisfaction.